Children With Developmental Coordination Disorder Exhibit Greater Stepping Error Despite Similar Gaze Patterns and State Anxiety Levels to Their Typically Developing Peers - Parr, Johnny V. V.; Foster, Richard J.; Wood, Greg; Hollands, Mark A. (Frontiers in Human Neuroscience, 2020)
This study examined stepping accuracy, gaze behaviour and state-anxiety in children with (N = 21, age M = 10.81, SD = 1.89) and without (N = 18, age M = 11.39, SD = 2.06) developmental coordination disorder (DCD) during an adaptive locomotion task. Participants walked at a self-selected pace along a pathway, placing their foot into a raised rectangular floor-based target box followed by either no obstacles, one obstacle, or two obstacles. Stepping kinematics and accuracy were determined using three-dimensional motion capture, whilst gaze was determined using mobile eye-tracking equipment. The children with DCD displayed greater foot placement error and variability when placing their foot within the target box and were more likely to make contact with its edges than their typically developing (TD) peers. The DCD group also displayed greater variability in the length and width of their steps in the approach to the target box. No differences were observed between groups in any of the gaze variables measured, in mediolateral velocity of the centre of mass during the swing phase into the target box, or in the levels of self-reported state-anxiety experienced prior to facing each task. We, therefore, provide the first quantifiable evidence that deficits to foot placement accuracy and precision may be partially responsible for the increased incidence of trips and falls in DCD, and that these deficits are likely to occur independently from gaze behaviour and state-anxiety.